A top-down view of the tumor microenvironment: structure, cells and signaling - Bhome, Rahul; Bullock, Marc D.; Al Saihati, Hajir A.; Goh, Rebecca W.; Primrose, John N.; Sayan, A. Emre; Mirnezami, Alex H. (Frontiers in Cell and Developmental Biology, 2015)
It is well established that the tumour microenvironment contributes to cancer progression. Stromal cells can be divided into mesenchymal, vascular and immune. Signalling molecules secreted by the tumour corrupts these cells to create ‘activated’ stroma. Equally, the extracellular matrix contributes to tumour development and invasion by forming a biologically active scaffold. In this review we describe the key structural, cellular and signalling components of the tumour microenvironment with a perspective on stromal soluble factors and microRNAs.